Exchange bias associated with phase separation in the Nd2/3Ca1/3MnO3 manganite - Fertman, Elena; Dolya, Sergiy; Desnenko, Vladimir; Kajňaková, Marcela; Feher, Alexander (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
The exchange bias (EB) phenomenon has been found in Nd2/3Ca1/3MnO3 perovskite. The phenomenon manifests itself as a negative horizontal shift of magnetization hysteresis loops. The EB phenomenon is evident of an interface exchange coupling between coexisting antiferromagnetic (AFM) and ferromagnetic (FM) phases and confirms the phase separated state of the compound at low temperatures. The EB effect is found to be strongly dependent on the cooling magnetic field and the temperature, which is associated with the evolution of spontaneous AFM–FM phase separated state of the compound. Analysis of magnetic hysteresis loops has shown that ferromagnetic moment MFM originating from the FM clusters saturates in a relatively low magnetic field about H 0.4 T. The obtained saturation value MFM (1 T) 0.45 μB is in a good agreement with our previous neutron diffraction data.